Strains of Coniothyrium minitans reduce the emission of apothecia of Sclerotinia sclerotiorum - Morandi, Marcelo Augusto Boechat; Silva, Carlos Eduardo Oliveira [UNESP]; Costa, Lúcio Bertoldo; Bettiol, Wagner (My University, 2012)
Sclerotia of Sclerotinia sclerotiorum (Ss) can survive for long time in soil and are the main inoculum source of the white mold disease. An alternative for reducing this inoculum is the use of parasites, such as Coniothyrium minitans (Cm). We evaluated the potential of Cm isolates for the biological control of Ss in beans. The effect of the temperature on the growth of 15 isolated of Cm was evaluated in vitro. The hyperparasitism ability of Cm was evaluated in soil infested with sclerotia and conditioned in pots. The infested soil was treated with conidia suspension of the antagonists, fluazinan or sterile distilled water. After seven days at 20°C, the sclerotia were removed from soil and placed inside Petri dishes over bean leaves previously disinfested. The germination and parasitism of sclerotia were evaluated after 7 to 10 days. To evaluate the apothecia emission, soil infested with sclerotia of Ss and treated as described was maintained at 18°C and the number of emerged apothecia was counted up to 84 days after inoculation. The emergence of bean plants in soil infested with sclerotia and mycelium of the pathogen and treated as described was evaluated in greenhouse. The ideal temperature for growth of Cm isolates varied from 18 to 19°C and at 30-35°C they were complete inhibited. The isolates of Cm promoted less than 10% of reduction in viability of the sclerotia, but they significantly reduced the emission of apothecia. Two isolates increased the emergence of plants in relation to the inoculated check, but was significantly lower than the non-inoculated check. Field tests will be conduct to confirm the potential of the selected isolates to reduce the inoculum source of the pathogen.
Keywords: Beans; Biological control; Soilborne pathogen